2022
DOI: 10.1111/jjns.12479
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a professional identity promotion strategy for nursing students during the COVID‐19 pandemic: A quasi‐experimental study

Abstract: Aim To evaluate the effectiveness of a professional identity promotion strategy (PIPS) on nursing students' professional identity and resilience. Methods This study was a quasi‐experimental study with a random cluster sample of 103 sophomore undergraduate nursing students. One hundred students answered the questionnaires at both baseline and follow‐up (51 of 53 in the intervention group and 49 of 50 in the control group). Intervention and control groups underwent 5 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…The results of the study show that the professionalism of nursing students is at a medium level and needs to be improved, which may be related to the fact that nurses in our country are not valued and have low social status (Qi et al, 2021 , Wang, 2022 ). The data showed that nursing students who are willing to change majors have a lower level of professionalism, which is consistent with previous research results.…”
Section: Discussionmentioning
confidence: 98%
“…The results of the study show that the professionalism of nursing students is at a medium level and needs to be improved, which may be related to the fact that nurses in our country are not valued and have low social status (Qi et al, 2021 , Wang, 2022 ). The data showed that nursing students who are willing to change majors have a lower level of professionalism, which is consistent with previous research results.…”
Section: Discussionmentioning
confidence: 98%
“…More interpersonal practice and simulation activities may encourage freshmen to communicate with others. Finally, nursing teachers may use psychological intervention strategies to promote the formation of PI and ISS among FNSs, such as cognition intervention, group psychological intervention, and empathy intervention ( Wang et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In China, nurses have always been treated as having low levels of education, a high-pressure working environment, and low social status ( Zhang et al, 2021 ). As a result, the nursing profession is not the first choice of many Chinese freshman nursing students (FNSs), but it is often chosen due to course allocation in colleges being based on student preferences (generally, nursing courses are the least preferred by students) or based on others’ recommendation ( Wang et al, 2022 ). Many students switch to other medical majors in their sophomore year or relinquish their nursing professional education in the senior year ( Wang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…48,63 Meta-analysis of 13 trials with 990 participants showed resilience interventions improved resilience moderately (pooled SMD 0.74, 95%CI 0.03 to 1.46, I 2 96%) (Figure 2a) compared to sham or no intervention. 48,[51][52][53][54]57,58,63,[66][67][68][69] Data in one study contained two independent comparisons (i.e. with no participants in common) based on baseline characteristics and therefore appears twice to include all participants.…”
Section: Effects Of Intervention On Resiliencementioning
confidence: 99%